Evaluation of dermatologic adverse events associated with aromatase inhibitors: insights from the FAERS database - Wu, Yuan-Yuan; Huang, Qiong-Lian; Luo, Zhan-Yang; Song, Xiao-Yun; Shi, You-Yang; Zheng, Jin-Zhou; Liu, Sheng (Frontiers in Pharmacology, 2025)
BackgroundThis study evaluates the risk of dermatologic adverse events (AEs) associated with aromatase inhibitors (AIs) through an analysis of data from the FDA Adverse Event Reporting System (FAERS).MethodsFAERS data from Q1 2004 to Q2 2024 were analyzed for dermatologic AEs related to AIs. A disproportionality analysis using reporting odds ratio (ROR) assessed AE risk, and the time to onset of these AEs was examined.ResultsOut of 21,035,995 AE reports, 2,237 involved skin impairment. Sixty-one preferred terms (PTs) presented positive signals, including nail disorders, onychoclasis, and abnormal hair growth in patients on anastrozole, exemestane, or letrozole. The highest associations were with pseudo cellulitis (ROR = 57.73), anhidrosis (ROR = 48.68), and nail toxicity (ROR = 38.40). Strong associations were observed for anastrozole (ROR = 1.07, 95% confidence interval: 1.03–1.11) and exemestane (ROR = 1.1, 95% CI: 1.04–1.16), but not for letrozole. Eleven dermatologic PTs had onset times under 50 days, with the earliest at 2 days; the latest, skin ulcer, appeared at 241.5 days with exemestane.ConclusionThe findings provide substantial evidence of dermatologic AEs associated with AIs, particularly anastrozole and exemestane, emphasizing the importance of dermatologic monitoring during AI therapy and the need for further research into AI-induced dermatologic AEs.